Oye Loca : From the Mariel Boatlift to Gay Cuban Miami - Peña, Susana, 1972- (Book collections on Project MUSE., 2013)
During a few months in 1980, 125,000 Cubans entered the U.S. as part of a massive migration known as the Mariel boatlift. Drawing from first-person stories of Cuban Americans, as well as government documents and cultural texts from both the U.S. and Cuba, the author reveals how a single historical event shaped the formation of an entire ethnic and sexual landscape.